Skull Sutures and Cranial Mechanics in the Permian Reptile Captorhinus aguti and the Evolution of the Temporal Region in Early Amniotes - Abel, Pascal; Pommery, Yannick; Ford, David Paul; Koyabu, Daisuke; Werneburg, Ingmar (Frontiers in Ecology and Evolution, 2022)
While most early limbed vertebrates possessed a fully-roofed dermatocranium in their temporal skull region, temporal fenestrae and excavations evolved independently at least twice in the earliest amniotes, with several different variations in shape and position of the openings. Yet, the specific drivers behind this evolution have been only barely understood. It has been mostly explained by adaptations of the feeding apparatus as a response to new functional demands in the terrestrial realm, including a rearrangement of the jaw musculature as well as changes in strain distribution. Temporal fenestrae have been retained in most extant amniotes but have also been lost again, notably in turtles. However, even turtles do not represent an optimal analog for the condition in the ancestral amniote, highlighting the necessity to examine Paleozoic fossil material. Here, we describe in detail the sutures in the dermatocranium of the Permian reptile Captorhinus aguti (Amniota, Captorhinidae) to illustrate bone integrity in an early non-fenestrated amniote skull. We reconstruct the jaw adductor musculature and discuss its relation to intracranial articulations and bone flexibility within the temporal region. Lastly, we examine whether the reconstructed cranial mechanics in C. aguti could be treated as a model for the ancestor of fenestrated amniotes. We show that C. aguti likely exhibited a reduced loading in the areas at the intersection of jugal, squamosal, and postorbital, as well as at the contact between parietal and postorbital. We argue that these ‘weak’ areas are prone for the development of temporal openings and may be treated as the possible precursors for infratemporal and supratemporal fenestrae in early amniotes. These findings provide a good basis for future studies on other non-fenestrated taxa close to the amniote base, for example diadectomorphs or ‘protorothyridids’.